Text Comprehension in Good and Poor Readers: Cognitive and Linguistic Aspects - Balčiūnienė, Ingrida; Kornev, Aleksandr N.; Oganov, Sergej R. (Kalbotyra, 2015)
The paper deals with a comprehension of written text in young Russian-speaking adults. Theoretical background was based on the 3-level model of text processing (van Dijk, Kintsch 1983). The study aimed at comparing qualitative features and quantitative measures of text comprehension in good and poor readers. During the first stage of the study, all the subjects (N = 40) were performed three reading comprehension tasks and three psychological tests for intelligence, verbal reasoning and working memory assessment. Then, after statistical analysis, two groups of subjects were formed for the second stage of the study. Group 1 (N = 11) comprised the subjects whose text comprehension skills were above 85 percentiles (so called ‘good readers’) and Group 2 (N = 8) comprised those whose results were below 15 percentiles (so called “poor readers”). During the second stage of the study, the subjects performed reading task based on a keyword methodology. Four texts (almost equal in a length), i.e. two scientific expository texts and two narratives, were presented to each of the subjects to develop a list of ten keywords. The subjects also were asked four complex content questions related to the main points of each of the texts. Statistical analysis revealed significant difference between the groups in the keywords lists and in questions answering scores. Psychological assessment revealed statistically significant difference between the groups in all tested cognitive measures. These results evidenced that the poor readers distinct from the good readers both in text processing strategy and in cognitive functioning. These results are in close agreement with other studies of reading comprehension. The study was based on a data of Russian-speaking population, but the results might be important also for Lithuanian (psycho-) linguists and practicians whose professional activity includes assessment of written text comprehension ant its disorders.
Keywords: text comprehension; quantitative approach; keywords; Russian